Relationship between physical activity and cognitive function in apparently healthy young to middle-aged adults: A systematic review. Issue 8 (August 2016) - Cox, Eka Peng; O'Dwyer, Nicholas; Cook, Rebecca; Vetter, Melanie; Cheng, Hoi Lun; Rooney, Kieron; O'Connor, Helen
Abstract: Objectives : There is increasing evidence that physical activity (PA) positively affects cognitive function (CF). Existing research has focussed on this association in children and the elderly, with less research available in young to middle-aged adults who constitute a substantial proportion of the population. Design : A systematic review investigating the relationship between habitual PA (≥12 months) and CF in young to middle-aged adults (18–50 years). Methods : A search was conducted using AMED, CINAHL, MEDLINE, PsychINFO, AUSPORT MED and SPORTDiscus databases. Eligible studies had to report descriptive statistics for CF and PA levels in healthy participants 18–50 years. Effect sizes (ES) (Hedges g) were calculated where possible. Results : The initial search netted 26, 988 potentially relevant manuscripts, with four more identified through hand searching. Fourteen were included for review. A range of validated platforms assessed CF across three domains: executive function (12 studies), memory (four studies) and processing speed (seven studies). Habitual PA was assessed via questionnaire/self-report methods ( n = 13, 8 validated) or accelerometers ( n = 1). In studies of executive function, five found a significant ES in favour of higher PA, ranging from small to large. Although three of four studies in the memory domain reported a significant benefit of higher PA, there was only one significant ES, which favoured low PA. Only one study examining processing speed had a significant ES, favouring higher PA. Conclusions : A limited body of evidence supports a positive effect of PA on CF in young to middle-aged adults. Further research into this relationship at this age stage is warranted.